2022
DOI: 10.1128/spectrum.01881-21
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of NBS1/MRN Complex Formation by E4orf3 Supports NF-κB That Licenses E1B55K-Deleted Adenovirus-Infected Cells to Accumulate DNA>4n

Abstract: Genome instability, a hallmark of cancer, exists as part of a cycle that leads to DNA damage and DNA > 4n that further enhances genome instability. Ad E4orf3 is a viral oncogene. Here, we describe E4orf3 mediated signaling events that support DNA > 4n in Δ E1B Ad-infected cells. These signaling events may be linked to the oncogenic potential of E4orf3 and may provide a basis for how some cells survive with DNA > 4n.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 86 publications
2
6
0
Order By: Relevance
“…In other cell systems, Akt allows the activation of mTOR1 that mediates the phosphorylation activation of NF-kB [51]. In a recent publication we provide further evidence supporting a link between E4orf1 and activation of NF-kB [17] which is known for its involvement in the induction of innate cytokine genes important for stimulating both innate and adaptive arms of the immune system [16]. Moreover, we showed that E4orf1-deleted ∆E4 1 Ad-immunized rhesus macaques produced higher levels of IFNγ-producing memory T-cells (Figure 4), higher levels of transgene-specific IgG1 (Figure 6), and antibodies able to mediate greater ADCC activity (Figure 8) than the E4orf1containting ∆E1B parental Ad.…”
Section: Discussionsupporting
confidence: 58%
See 3 more Smart Citations
“…In other cell systems, Akt allows the activation of mTOR1 that mediates the phosphorylation activation of NF-kB [51]. In a recent publication we provide further evidence supporting a link between E4orf1 and activation of NF-kB [17] which is known for its involvement in the induction of innate cytokine genes important for stimulating both innate and adaptive arms of the immune system [16]. Moreover, we showed that E4orf1-deleted ∆E4 1 Ad-immunized rhesus macaques produced higher levels of IFNγ-producing memory T-cells (Figure 4), higher levels of transgene-specific IgG1 (Figure 6), and antibodies able to mediate greater ADCC activity (Figure 8) than the E4orf1containting ∆E1B parental Ad.…”
Section: Discussionsupporting
confidence: 58%
“…In Figure 2B, HeLa cells were infected with the ∆E1B Ad and treated 4 h later with or without AktIV, known to prevent the phosphorylation of Akt. The same antibodies used in Figure 2A did not recognize phosphorylated Akt in AktIV-treated ∆E1B Ad infected cells, confirming the antibody specificity and supporting the notion that cells infected with ∆E3 or ∆E1B Ad contain phosphorylated Akt (Ser473 and Thr308), in stark contrast to cells infected with ∆E4 1 Ad (Figure 2A, [13,17]). A PCR for the Ad fiber gene (Figure 2B) was used to confirm infection of the cells.…”
Section: E4orf1 Limits Intrinsic Innate Cytokine Gene Expression In ∆...supporting
confidence: 67%
See 2 more Smart Citations
“…Recently, Sangare and co-authors identified E4orf1 as a co-factor with E1B–55K that limited the immune response, since rhesus macaques immunized by an E1B–55K- and E4orf1-deleted HAdV-C5 vector produced higher levels of HIV-envelope-specific interferon γ-producing memory T-cells, higher titers of specific IgG1 binding antibody, and antibodies that were able to mediate antibody-dependent cellular cytotoxicity with greater killing capacity than the original deleted E1B–55K vector [ 25 ]. Since the PI3K-Akt-mTOR pathway also mediates immune responses through activating the NF-κB-mediated transcription of cytokine genes that are important for stimulating innate and adaptive parts of the immune system, E4orf1 activation of PI3K may also induce NF-κB and seems to be involved in HAdV-C5 vector system immune response signaling [ 25 , [343] , [344] , [345] ]. Although it remains to be investigated to what degree E4orf1 is “active” within AdV vectors, these studies indicate that the inclusion of the E4orf1 coding region clearly affects immunogenicity and oncolysis of these vectors [ 25 , 327 ].…”
Section: Biotechnological Adv Vector Applications and The Role Of E4orf1mentioning
confidence: 99%